Studies on dispersion and reactivity of vanadium oxides deposited on lamellar ferrierite zeolites for condensation of glycerol into bulky products - Vieira, Luiz H. [UNESP]; Possato, Luiz G. [UNESP]; Chaves, Thiago F. [UNESP]; Pulcinelli, Sandra H. [UNESP]; Santilli, Celso V. [UNESP]; Martins, Leandro [UNESP] (Elsevier, 2018)
The acetalization of acetone with glycerol was investigated using vanadium-impregnated catalysts. The siliceous supports FER, a purely microporous material, and ITQ-6, a micro/mesoporous material, were obtained from a ferrierite lamellar precursor, PreFER. Both supports were impregnated with 1, 5 or 10 wt.% of vanadium. The structural properties were characterized by X-ray diffraction and N2 adsorption/desorption, the dispersion and speciation of surface vanadium were analyzed by diffuse reflectance UV–vis spectroscopy and X-ray absorption spectroscopy (XANES and EXAFS), and the total acidities of the catalysts were evaluated by temperature-programmed NH3 desorption. The [5V]Si-ITQ-6 and [10V]Si-ITQ-6 catalysts provided the best catalytic results, with conversions of 100 and 90%, respectively, and selectivity towards solketal of approximately 99%. The higher surface area generated by mesoporosity in the Si-ITQ-6 support, compared to the microporous Si-FER support, provided good access for the diffusion of reactants and products, and good dispersion of vanadium, even at high vanadium loadings (10 wt.%), with preferential formation of VO4 monomers and VOx oligomers on the surface. The greater contributions of these species to the total acidities of the catalysts resulted in higher catalytic activities, compared to the effect of V2O5 agglomerates.
Keywords: FER structure; Glycerol condensation; Lamellar zeolites; Solketal; Vanadium